Determining Crispness Level of Dry Food through Its Compressive Strain Energy - Farid Triawan; Gloria Ellysian Aprilia; Kushendarsyah Saptaji; Ramadhona Saville; Asep Bayu Dani Nandiyanto (Faculty of Engineering and Technology, Sampoerna University, 2021)
Crispness is the most appealing characteristic of dry food products. However, the term crispness has different subjective meaning among consumers. This study aims to quantitatively measure the crispness of potato crisp by performing compression test on a single specimen, and analyzing the compressive behavior, i.e., compressive strain energy. The crispness of the specimens were differentiated by changing the moisture exposure durations, which are 0, 1, 2, 3, 6 hours, in a room and ambient condition. The measured load and displacement data were transformed into stress and strain curves. The strain energy for every 1% strain increment was calculated and investigated to determine the crispness. The crispness difference among specimens of 0, 3, and 6 hours groups was significantly perceived at 8% of strain. It was revealed that the 3 and 6 hours of room air exposure could decrease the crispness by 17% and 45%, respectively. This suggests the compressive strain energy at a certain strain can be an indicator of crispness. This experimental study is expected to evolve food engineering by proposing a simple yet precise crispness measurement method for dry food.